EFEKTIVITAS PENGELOLAAN DANA BOS DI SD NEGERI 1 BURAN DAN SD NEGERI 03 KALING KECAMATAN TASIKMADU KABUPATEN KARANGANYAR - WIDANINGSIH, SRI REJEKI (2011)
The study aims to reveal the effectiveness of School Operational Grants toward school management of SD Negeri 1 Buran dan SD Negeri 03 Kaling kecamatan Tasikmadu Kabupaten Karanganyar. Specifically, the objectives of the study are: 1) describe the management of school operational grants; 2) describe the effectiveness of the management of school operational grants; and 3) describe academic activity in the school following school operational grants. It is evaluation research for the implementation of a program particularly in its management. The model of evaluation is CIPP (Context-Input-Process- Product) due to the model directs evaluation target in its process through output. The techniques of collecting data are document, observation, and interview. The data are analyzed using data reduction, data display, and conclusion as well as verification. Result of the study shows that: 1) in managing school operational grants, planning is based on the agreement between school and school committee for funding activities, consisting of students funding, curriculum, and learning activity, educator and administrator, facilities, culture and school environment, and community participation as well as partnership; the fund is used for funding school operational needs, including staff wage, goods purchasing, maintenance, and other costs. The evaluation is conducted each period of time. The models of evaluation are attached monitoring, internal and external functional monitoring, auditing, and community monitoring; 2) School Operational Grant management in the both elementary school is effective in percentage of 98 based on the criteria, namely: a) objective, target, and principle of fund usage is elucidated clearly, b) educational background and and socioeconomic status of the receiver are entirely fulfill the requirements of the program, c) the uses of fund are for funding school operation, and d) school managemen in managing the grant is clear, transparent, and structured, and there is improvement of students' academic performance; 3) academic activities conducted in both schools are teachers and students development, involving teacher training, MGMP, and additional learning activities as well as extracurricular activity, and addition of textbooks and library collection in order to improve students' achievements.